2014
DOI: 10.1590/1415-52732014000100009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fatty Amazon fish consumption on lipid metabolism

Abstract: OBJECTIVE: The present study aimed to evaluate the effect of feeding diets enriched with fatty fish from the Amazon basin on lipid metabolism. METHODS: Male Wistar rats were divided into four groups: control group treated with commercial chow; Mapará group was fed diet enriched with Hypophthalmus edentatus; Matrinxã group was fed diet enriched with Brycon spp.; and, Tambaqui group was fed diet enriched with Colossoma macropomum. Rats with approximately 240g±0.60 of body weight were fed ad libitum for 30 days, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…TC and PAI increased significantly in the lyophilized group, but not with the consumption of enriched diet and coconut oil (Table 4). These results are similar to those of Amaral et al [64], who showed that the Wistar rats did not modify their total cholesterol levels in the groups treated with diets enriched with fatty fish from the Amazon. In contrast, in a study with Swiss albino mice supplemented with fatty acids derived from the Caryocar brasiliense walnut, TC and HDL-c increased with no changes in the atherogenic index and triacylglycerides [65].…”
Section: The Route Of Administration Is More Relevant Than Thesupporting
confidence: 92%
“…TC and PAI increased significantly in the lyophilized group, but not with the consumption of enriched diet and coconut oil (Table 4). These results are similar to those of Amaral et al [64], who showed that the Wistar rats did not modify their total cholesterol levels in the groups treated with diets enriched with fatty fish from the Amazon. In contrast, in a study with Swiss albino mice supplemented with fatty acids derived from the Caryocar brasiliense walnut, TC and HDL-c increased with no changes in the atherogenic index and triacylglycerides [65].…”
Section: The Route Of Administration Is More Relevant Than Thesupporting
confidence: 92%
“…[48] This is based on omega 6 and 3 ratio but also based on the fact that fatty Amazon fish can change the lipid metabolism effectively lowering plasma Low Density Lipoprotein (LDL) and increasing High Density Lipoprotein (HDL). [49] While when we interpreted in light of the crosstalk between the ecological environment and fish physiology, its fact that species sharing the same food habits can have similar substrates for the endogenous synthesis of lipids, these seem to be used to attend the specific fish metabolism. [50] Amazon fishes developed different adaptations to survive in the challenging environment of the region, such as migratory habits and mechanisms to deal with hypoxia exposure.…”
Section: Influnces On Lipids Composition and Distribution In Amazonian Fishesmentioning
confidence: 99%
“…The diets were prepared as recommended by Souza et al 19 . In summary, the fish muscle was deboned mechanically (Baader 694 Bone Separator) and immediately frozen to -30 o C. The bulk of the experimental diets wasthe commercial chow Nuvilab CR-1 (Nuvilab ® Nutrientes Ltda, Curitiba, PR).…”
Section: Diet Preparationmentioning
confidence: 99%